2022
DOI: 10.3390/polym15010183
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rapid Detection Method for Degradation Performance of Polyolefin-Based Degradable Plastics

Abstract: In order to accurately determine the degradation performance of polyolefin-based degradable plastics, the concept of bioassimilated carbon is proposed for the first time in this paper; the bioactive and hydrophilic organic carbon in plastic degradation products is defined as bioassimilation carbon. A method for the detection of the carbonyl index and bioassimilated carbon conversion rate in polyolefin degradable plastics was developed to quickly identify its degradation performance. The measurement results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This class of biodegradable polymers includes polycaprolactone (PCL), polyesteramides (PEA), aliphatic copolyesters (e.g., PBSA), etc. Besides, though debatable, some polymers with additives can also be classified as biodegradable polymers, such as polyolefin with pro-oxidant additives [25].…”
Section: Biodegradable Polymers Synthesized From Conventional Petrole...mentioning
confidence: 99%
“…This class of biodegradable polymers includes polycaprolactone (PCL), polyesteramides (PEA), aliphatic copolyesters (e.g., PBSA), etc. Besides, though debatable, some polymers with additives can also be classified as biodegradable polymers, such as polyolefin with pro-oxidant additives [25].…”
Section: Biodegradable Polymers Synthesized From Conventional Petrole...mentioning
confidence: 99%
“…In view of the fast consumption of non-renewable fossil fuels and the increasingly serious environment pollution caused by the extensive application of petroleum-based polymers, especially polyolefin plastics, developments in renewable-sourced and biodegradable polymers have been attracting great attention in the past decades [ 1 , 2 , 3 , 4 ]. Among the reported degradable polymers, poly(lactic acid) (PLA), readily synthesized from bio-mass, has been regarded as one of the most promising materials to substitute for conventional petroleum-based plastics thanks to its good strength and susceptibility to decompose via hydrolysis of ester groups.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradability is defined as the ability of a material to degrade into simple matter that can be metabolized by microorganisms as a carbon source under the required conditions [14]. The mechanism of plastic materials' biodegradation is yet to be established [15]. Research in the field has concluded so far that biodegradation occurs in three different steps: (i) development of a biofilm onto the polymeric surface; (ii) microorganisms' action towards the polymeric chain and its scission due to enzymatic mechanisms; (iii) metabolization of polymeric residues as carbon sources [16].…”
Section: Introductionmentioning
confidence: 99%